2019
DOI: 10.3390/ma12244178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Travel Speed on Microstructure and Mechanical Properties of FSW Joints for Al–Zn–Mg Alloy

Abstract: The microstructures and mechanical properties of friction stir welded (FSW) Al–Zn–Mg alloy plate under different travel speeds were investigated. Both the average grain sizes (AGSs) of the shoulder affected zone (SAZ), nugget zone (NZ), and the widths of thermo-mechanically affected zone (TMAZ) decreased with the increase of travel speed. Moreover, the AGSs of NZ are always about 60% of that of SAZ at different travel speeds. The fractions of high-angle grain boundaries (HAGBs) in the FSW joints reduce with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…σ a = 504.37(ε p ) 0.068 (6) The obtained value of the cyclic strength coefficient (504.37 MPa) is almost three times lower than for the base material (1518.1 MPa) [52]. Although, the decrease of cyclic strength coefficient is expected for welded joints, in this case, the reported drop is significant and the obtained value is similar to the values reported by research [31,36,[55][56][57].…”
Section: Low Cycle Fatigue Properties and Fracture Surface Observationssupporting
confidence: 82%
See 1 more Smart Citation
“…σ a = 504.37(ε p ) 0.068 (6) The obtained value of the cyclic strength coefficient (504.37 MPa) is almost three times lower than for the base material (1518.1 MPa) [52]. Although, the decrease of cyclic strength coefficient is expected for welded joints, in this case, the reported drop is significant and the obtained value is similar to the values reported by research [31,36,[55][56][57].…”
Section: Low Cycle Fatigue Properties and Fracture Surface Observationssupporting
confidence: 82%
“…Friction stir welding (FSW) is a very efficient technology in the production of aluminum alloy joints, as it provides a number of advantages over traditional fusion welding such as the lower temperature of the joining process [1][2][3]. This particular factor is crucial when it comes to welding of high-strength aluminum alloys, which are mainly precipitated-hardening materials (2XXX and 7XXX series) and their specific strength is an effect of thermally unstable precipitates (e.g., Guinier-Preston zones, θ phase) [4][5][6][7]. Considering the production of efficient welds of these materials, the losses in hardening must be taken into account due to the thermal affection of the joining process on the workpiece.…”
Section: Introductionmentioning
confidence: 99%
“…Tool rotational speed (TRS) and welding speed (WS) are the parameters that influence the weld joint quality. 64,65 However, tilt angle (TA), axial load (P), plunge depth (PD), etc. were also considered by many authors to attain superior welds.…”
Section: Fsw Factorsmentioning
confidence: 99%
“…It can be remarked from the hardness map that is described in blue color with a hardness value of about 29 HV (Figure 18a) at the 50 mm/min travel speed, and the color map changed to red color with hardness values around 36 HV (Figure 18d) using the Cy pin at the 300 mm/min travel speed. The correlations between microstructures and mechanical properties in terms of hardness and joint strength of the friction stir-welded aluminum alloys under different travel speeds have been studied in many works [39,40]. Increasing travel speeds can improve the mechanical properties of the friction stir welded joints through the enhancement of the material flow and plastic deformation [41,42], but extremely high travel speed can cause defects such as voids, tunnels, kissing bond, and lack of penetration due to the lack of heat input [43,44].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In contrast, extremely low travel speed promotes very high heat input, which can cause a serious softening manner in the weld zone. Lin et al [40] studied the effect of travel speed (50-200 mm/min) on the microstructure and mechanical properties of 12-mm thick Al-Zn-Mg alloy at a constant rotation speed of 450 rpm. They found that both the average grain sizes of the shoulder-affected zone, NZ, and the widths of TMAZ decreased with the increase of travel speed.…”
Section: Mechanical Propertiesmentioning
confidence: 99%